Translation, cultural adaptation and validation of perceived nutrition environment measures survey (nems-p) and Its relationship with the glycaemic values (HBA1C) among diabetic patients in Kuala Terengganu district - Berahim, Ahmad Syaify (2024)
The perceptions of diabetic patients on their food environment influence their dietary choices and may impact glycaemic control. The Perceived Nutrition Environment Measures Surveys (NEMS-P) questionnaire is a valid and reliable measure to access perceived food environment. To date, there is no available instrument to measure the perceived food environment in Malaysia and its association with the level of glycaemic control among diabetic patients. Objectives: This study aimed to translate, culturally adapt and validate Malay version of NEMS-P, and to study the relationship between the perceived food environments and the glycaemic values among diabetic patients attending health clinics in Kuala Terengganu district. Methodology: Phase 1 study involved translation, cultural adaptation and validation of the NEMS-P within Malay context. Confirmatory factor analysis (CFA) was conducted involving 200 diabetic patients in Kuala Terengganu and were randomly selected by multi-staged sampling and interviewed using the NEMS-P (Malay). Phase 2 was a cross-sectional study involving 304 diabetic patients and were selected from all three health clinics in Kuala Terengganu by applying the stratified sampling proportional to size method and utilising the validated NEMS-P (Malay). Linear Regression was used for the analysis. Results: The average Content Validity Ratio (CVR) was 0.90, the Scale Content Validity Index (S-CVI) for relevance was 0.81 and the S-CVI for clarity was 0.96, both scale face validity index (S-FVI) for clarity and comprehension were 0.97 and all were acceptable. The constructs which were included in CFA were perceived store consumer environment (PSCE), perceived restaurant consumer environment (PRCE) and perceived home food environment (PHFE) but perceived community nutrition environment (PCNE) was excluded as it did not require construct analysis. The factor loading ranged from 0.3 to 0.9 and the model had acceptable fit. The construct reliability (CR) values ranged from 0.614 to 0.778, the average variance extracted (AVE) 0.171 to 0.469. One inter-factor correlation value was higher than the square root of average variance extracted (AVE). For phase 2, 68.8% of respondents were females with the mean age of 58.77 (SD 10.57). Most respondents entered secondary school (57.9%), married individuals (69.7%) and overweight or obese (72.0%). The proportion of smokers was low (7.6%). All four perceived food environment constructs were included for scoring. The mean score for the PCNE was 9.70 (SD 2.71), PSCE was 37.60 (SD 3.82), PRCE was 4.28 (SD 3.11) and PHFE was 19.53 (SD 4.95). The mean duration (years) of diabetes was 6.71 (SD 5.78) with the mean HbA1c (%) of 8.09 (SD 2.14). There was no significant association between perceived food environments and glycaemic values. Instead, there were other statistically significant factors; age [-0.05% (95% CI: -0.075, -0.025 p-value: 0.001)], married [1.42% (95% CI: 0.407, 2.429 p-value: 0.006)], divorced/separated [1.20% (95% CI: 0.063, 2.331 p-value: 0.039)], smoking [1.25% (95% CI: 0.377, 2.128 p-value: 0.005)] and duration of diabetes [0.10% (95% CI: 0.052, 0.137 p-value: 0.001)]. Conclusion: Malay version of NEMS-P questionnaire is a valid and reliable tool to measure perceived food environment in Kuala Terengganu. There was no statistically significant relationship between perceived food environments and HbA1c values, indicating the need for future research with a more heterogeneous and diverse population.